Hepatitis B virus infections in pregnant women and children in the era of HBV elimination - Pawlowska, Malgorzata (Clinical and Experimental Hepatology, 2024)
In the hepatitis B virus (HBV) elimination strategy announced by the World Health Organization (WHO) in 2016, one of the main aspects is the prevention of vertical infections. In the prevention of vertical HBV infections, chemoprophylaxis with tenofovir is recommended from the 28 th week of pregnancy in women with a high viral load (HBV DNA > 2 × 10 5 IU/ml) or the presence of HBeAg in the serum and active-passive immunoprophylaxis (HepB-BD+ HBIG) in all newborns born to mothers infected with HBV. Attention was paid to the incidence of latent HBV infections among children and adolescents and the role of the vaccine dose and additional hepatitis B booster vaccination in the prevention of HBV, especially in highly endemic areas and risk groups. The role of the age of initiation of therapy in the context of functional cure was indicated.